Studi Kondisi Kesiapan Koni Kab.Bangka Barat Dalam Pelaksanaan PORPROV Ke-Vi Di Bangka Barat - Fathdhail Muhaddisien; Ramanata Disurya; Hengki Kumbara (Journal on Education, 2023)
The problem in this study is, How is the condition of readiness of Koni Kab.Bangka Barat in preparing athletes in the aspect of athlete selection, How is the condition of readiness of Koni Kab.Bangka Barat in preparing athletes in the aspect of coaching programs, How is the condition of readiness of Koni Kab.Bangka Barat in preparing athletes in the aspect of nutrition, How is the condition of readiness of Koni Kab.Bangka Barat in preparing athletes in the aspect of awards? The purpose of this study was to determine the preparation of KONI in fostering athletes in the VIth PORPROV competition in West Bangka. In this study using qualitative methods with survey techniques. Data collection techniques in this study using observation, interviews and documentation. Based on the results of the study, it can be concluded that Koni Bangka Barat has met the readiness in the VIth Porprov championship held in West Bangka from various aspects of athlete selection, athlete programs, nutrition for athletes, and even awards.